EVOLUTION OF THE NATURALLY DEFORMED DUNITE FABRIC UPON MELTING UNDER ORIENTED COMPRESSION - Simonov V.A.; Goncharenko A.I.; Chernyshov A.I. (My University, 1988)
Little is known about the evolution of the olivine fabric pattern in naturally deformed ultramafic rocks. Moreover, it is especially important to ascertain the trends of variation of the olivine fabric because peridotite in the upper mantle might undergo partial melting under structurally controlled conditions. For this purpose, an oriented dunite sample from the core of the Middle Ters' pluton was subject to axial compression for 30 minutes at high temperature in a piston and cylinder unit with an internal heater. The compression axis coincided with the direction of the γ maximum of olivine within the 8-percent density contour. Tests were run at temperatures from 1° to 1500°C and at pressures of 4 to 10 kb. The change from brittle failure to plastic flow in olivine was recorded at about 800°C. It was found that under axial compression, the olivine fabric in plastically deformed dunite is greatly transformed and, upon melting of the latter, evolves into a special type of preferred orientation of the grain shape. Additional study results are discussed.